Determinants of Contraceptive Usage among Married Women in Shiraz, Iran - Khadijeh Asadisarvestani; Suet Khoo; Noor Malek; Suziana Yasin; Aliyar Ahmadi (Mashhad University of Medical Sciences, 2017)
Background & aim: Contraceptive usage is a central part of the quality of care in the provision of family services. Currently, this issue has gained much importance since the Iranian policy makers are changing their policies about family planning and contraceptives accessibility. Regarding this, the aim of this study was to determine the rate of contraceptive usage and the factors affecting contraceptive use among the married women of reproductive age in Shiraz County, Iran. Methods: This cross-sectional study was conducted on 626 married women of reproductive age (i.e., 15-49 years) living in Shiraz County (including Shiraz city and the rural areas) using the quantitative survey method. Sampling was performed using multi-stage cluster and purposive sampling techniques. The sample size was determined based on the Krejcie and Morgan's formula. The data were collected through a questionnaire filled out by some interviewers. Data analysis was performed both descriptively (i.e., frequency and percentage) and analytically (i.e., Chi-square and logistic regression tests) using the SPSS version 20. Results: According to the results of this study, the main predictors of contraceptive usage were couple agreement on contraception method, the number of actual births, women's authority, knowledge and positive attitude about contraceptives, and the number of desired children. Conclusion: Regarding the new population policies, the Iranian policy makers should be aware of the different aspects of family planning programs, particularly those targeting the contraceptive usage.